Severe Mycobacterial Immune Reconstitution Inflammatory Syndrome (IRIS) in Advanced Human Immunodeficiency Virus (HIV) Has Features of Hemophagocytic Lymphohistiocytosis and Requires Prolonged Immune Suppression. (1st September 2022) - Rocco, Joseph M; Laidlaw, Elizabeth; Galindo, Frances; Anderson, Megan; Rupert, Adam; Higgins, Jeanette; Sortino, Ornella; Ortega-Villa, Ana M; Sheikh, Virginia; Roby, Gregg; Kuriakose, Safia; Lisco, Andrea; et al.
Abstract: Background: People with HIV and mycobacterial infections can develop immune reconstitution inflammatory syndrome (IRIS) after starting antiretroviral therapy (ART). Severe mycobacterial IRIS has an overlapping clinical phenotype with hemophagocytic lymphohistiocytosis (HLH). We evaluated the pathophysiologic similarities between mycobacterial IRIS and HLH to identify clinical and immune predictors of mycobacterial IRIS severity. Methods: HLH criteria were applied to a longitudinal cohort of 80 patients with HIV (CD4 <100 cells/µL) and mycobacterial infections. Participants were subdivided into IRIS meeting HLH criteria (HLH-IRIS), IRIS without HLH (IRIS), and those without IRIS (non-IRIS). Clinical outcomes were evaluated by regression analyses. Soluble biomarkers and T-cell subsets were assessed at baseline and IRIS-equivalent time points. Results: HLH-IRIS patients required corticosteroids more frequently (OR: 21.5; 95%CI: 5.6–114.8) and for longer duration (21.2; 95%CI: 10.7–31.7 weeks) than those not meeting HLH criteria. Utilizing decision tree analyses, hemoglobin <9.2 g/dL was the best predictor of HLH-IRIS before ART, whereas ferritin, CXCL9 and sCD25 were most diagnostic for HLH at IRIS onset. At the IRIS timepoint, but not baseline, HLH-IRIS patients had lower regulatory and higher activated T cells along with greater production of IFNγ–IL-18 axis biomarkers compared with both IRIS and non-IRIS groups. Principal component analysis corroborated the distinct clustering of HLH-IRIS patients. Conclusions: Severe mycobacterial IRIS and HLH have an overlapping pathogenesis involving IFNγ and unopposed T-cell activation causing severe inflammatory disease clinically distinguished by hyperferritinemia (hyperferritinemic IRIS [FIRIS]). Hemoglobin, ferritin, CXCL9, and sCD25 identify high-risk patients and may improve risk stratification and therapeutic strategies for mycobacterial IRIS. Abstract : Severe mycobacterial IRIS in HIV can cause secondary HLH driven by pathologic IFNγ production and T-cell activation, leading to worse outcomes. Increased ferritin, anemia, CXCL9, and sCD25 associate with this phenotype and may be used for risk stratification and treatment optimization.